Bacterial pneumonia and its associated factors in children from a developing country: A prospective cohort study. - Anna Marie Nathan; Cindy Shuan Ju Teh; Kartini Abdul Jabar; Boon Teong Teoh; Anithaa Tangaperumal; Caroline Westerhout; Rafdzah Zaki; Kah Peng Eg; Surendran Thavagnanam; Jessie Anne de Bruyne (PLoS ONE, 2020)
INTRODUCTION:Pneumonia in children is a common disease yet determining its aetiology remains elusive. OBJECTIVES:To determine the a) aetiology, b) factors associated with bacterial pneumonia and c) association between co-infections (bacteria + virus) and severity of disease, in children admitted with severe pneumonia. METHODS:A prospective cohort study involving children aged 1-month to 5-years admitted with very severe pneumonia, as per the WHO definition, over 2 years. Induced sputum and blood obtained within 24 hrs of admission were examined via PCR, immunofluorescence and culture to detect 17 bacteria/viruses. A designated radiologist read the chest radiographs. RESULTS:Three hundred patients with a mean (SD) age of 14 (±15) months old were recruited. Significant pathogens were detected in 62% of patients (n = 186). Viruses alone were detected in 23.7% (n = 71) with rhinovirus (31%), human metapneumovirus (HMP) [22.5%] and respiratory syncytial virus (RSV) [16.9%] being the commonest. Bacteria alone was detected in 25% (n = 75) with Haemophilus influenzae (29.3%), Staphylococcus aureus (24%) and Streptococcus pneumoniae (22.7%) being the commonest. Co-infections were seen in 13.3% (n = 40) of patients. Male gender (AdjOR 1.84 [95% CI 1.10, 3.05]) and presence of crepitations (AdjOR 2.27 [95% CI 1.12, 4.60]) were associated with bacterial infection. C-reactive protein (CRP) [p = 0.007]) was significantly higher in patients with co-infections but duration of hospitalization (p = 0.77) and requirement for supplemental respiratory support (p = 0.26) were not associated with co-infection. CONCLUSIONS:Bacteria remain an important cause of very severe pneumonia in developing countries with one in four children admitted isolating bacteria alone. Male gender and presence of crepitations were significantly associated with bacterial aetiology. Co-infection was associated with a higher CRP but no other parameters of severe clinical illness.